As simple as it seems - Weeks, Sarah (Laura Geringer Books, 2010)
Eleven-year-old Verbena Polter gets through a difficult summer of turbulent emotions and the revelation of a disturbing family secret with an odd new friend who believes she is the ghost of a girl who drowned many years before.